Encyclopedia of Military Aircrafts - Valadez, Arnoldo, author 646445 (Delhi, India : Library Press : World Technologies, 2012)
A military aircraft is any fixed-wing or rotary-wing aircraft that is operated by a legal or insurrectionary armed service of any type. Military aircraft can be either combat or non combat: - Combat aircraft are aircraft designed to destroy enemy equipment using their own armament. Combat aircraft are normally developed and procured only by military forces. - Non-combat aircraft are aircraft not designed for combat as their primary . function, but may carry weapons for self-defense. These mainly operate in support roles, and may be developed by either military forces or civilian organizations.